ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN PERBANKAN DI INDONESIA (Studi Pada Bank Umum Swasta Devisa dan Non Devisa Periode 2012-2016) - Yurivin, Nerissa; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2018)
Banking is a business entity that has the task of rasing funds from public in the form of credits and/or others forms in order to improve the lives of many people. Private banks, especially Foreign Exchange and Non-Foreign Exchange in Indonesia are susceptible to financial distress, one of which is reflected in the decreasing level of net income. This study aims to find out the influence of CAMEL ratio proxied by Capital Adequacy Ratio, Non Performing Loan, Operational Cost for Operating Income, Return on Asset, and Loan to Deposit Ratio on Foreign Exchange Banks and Non-Foreign Exchange Banks against financial distress.The sample used in this research comes from Foreign Exchange Banks and Non-Foreign Exchange Banks listed on Indonesia Stock Exchange from 2012 to 2016, which is then selected by using purposive sampling technique. The number of samples obtained is 55 samples with 5 years time of observation. The samples obtained were processed using logistic regression model, after the previous goodness of fit test was done to test the feasibility of the data.The results of this study indicate Non Performing Loan and Return on Asset have an influence on the financial distress of Foreign Exchange and Non-Foreign Exchange Banking. Meanwhile, Capital Adequacy Ratio, Operational Cost for Operating Income and Loan to Deposit Ratio have no influence on the financial distress of Foreign Exchange and Non-Foreign Exchange Banking. In this test we get goodness of fit test result of 57,5% for Nagelkerke’s R Square test and 93,1% for Hosmer test and Lameshow’s goodness fit model.